Termelői szervezetek zöldség-gyümölcs kisárutermelőket integráló szerepe a nagy kereskedelmi láncoknak történő értékesítésben - Anita Kozak; János Felföldi; Antal Seres; Márton Szabó (Hungarian Academy of Sciences, Institute of Economics, 2011)
– The majority of the small-scale fruit and vegetable producers due to their small sizes are not able to meet the requirements of the large commercial chains by themselves. Only the cooperation could bring an effective solution. The POs are able to concentrate the scatteredsmall-scale commercial production and to supply as well as to homogenise all these. Furthermore, they are capable to provide activities, which a small-scale producer would not be able to undertake by itself. POs are the organisations which can become successful suppliers and due to their strong bargaining power also partners of the large commercial chains. The great number of small-scale producers can primarily become suppliers if they join these organisations. The POs are not yet frequent in the Hungarian fruit and vegetable sector; therefore, they do not play such a role in supplying to the large commercial chains as in the other Member States of the European Union. This is the fundamental reason of the difficulties encountered by the small-scale producers in supplying. The main reason of the difficulties between the successful Member States and Hungary is the significant share of the grey economy. On the one hand, it does not encourage the small-scale producers and on the other hand, it withdraws a large volume of goods from the legal sales channels through the POs.
Keywords: Q13; 330; commerce; concentration; large commercial chains; fruit and vegetable Producer Organisations; Gemüsebau; Obstbau; Landwirtschaftliche Betriebsform; KMU; Unternehmenskonzentration; Handelskette; Ungarn